A 206-nm all-solid-state deep-ultraviolet laser with 291 MW peak power - Ran, Qiandong; Short, Joel Stephen; Wang, Qi Jie; Li, Hao (Frontiers in Physics, 2023)
We successfully demonstrate the generation of an all-solid-state deep-ultraviolet (DUV) laser at 206 nm through the fifth (4 + 1)-harmonic generation using a 197-W, 10-kHz, 1.2-ps, 1,030-nm Yb:YAG laser. The DUV laser delivers 180 μJ–582 fs pulses with a peak power of 291 MW, which, to the best of our knowledge, is the highest peak power at 206 nm ever produced by all-solid-state kHz DUV laser sources driven at 1 μm wavelength. This corresponds to one order of magnitude improvement from early state-of-the-art record reported in the literature.